The Schumpeter Prize (Quarterly Journal of Economics, 1960)
The Schumpeter Prize Get access The Quarterly Journal of Economics, Volume 74, Issue 3, August 1960, Page 500, https://doi.org/10.1093/qje/74.3.500 Published: 01 August 1960